Heroes of history - Ganeri, Anita, 1961-; Barber, Nicola (Little Bee Books, 2015)
History doesn't just happen. It is made by amazing and extraordinary people! Explore the lives of twenty-four of the world's most outstanding individuals through engaging narratives, entertaining fictionalized diary entries, and informative timelines.